2012
DOI: 10.1002/smll.201202174
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Spores: Cytocompatible Encapsulation of Individual Living Cells within Thin, Tough Artificial Shells

Abstract: Cells are encapsulated individually within thin and tough shells in a cytocompatible way, by mimicking the structure of bacterial endospores that survive under hostile conditions. The 3D 'cell-in-shell' structures-coined as 'artificial spores'-enable modulation and control over cellular metabolism, such as control of cell division, resistance to external stresses, and surface-functionalizability, providing a useful platform for applications, including cell-based sensors, cell therapy, regenerative medicine, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(76 citation statements)
references
References 84 publications
0
75
0
1
Order By: Relevance
“…, formation of “cell-in-shell” structures) is to temporarily protect the cells against external stress during manipulation and storage, and to endow the cells with exogenous properties, magnetism in this work31323334. Living cells are generally vulnerable to chemical materials and treatments, and, therefore coating materials and procedures should be cytocompatible35363738394041.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, formation of “cell-in-shell” structures) is to temporarily protect the cells against external stress during manipulation and storage, and to endow the cells with exogenous properties, magnetism in this work31323334. Living cells are generally vulnerable to chemical materials and treatments, and, therefore coating materials and procedures should be cytocompatible35363738394041.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the cell magnetization has so far been limited to binary systems (yes and no from magnetized and non-magnetized cells), but “multinary” magnetization of living cells would allow for multi-level control of magnetized cells. We also envisioned that the multinary incorporation of magnetic nanomaterials into artificial spores (cell-in-shell structures)3132333435 would provide an advanced tool for manipulating the cellular hybrid structures at the single-cell level. In this work, we developed a simple but versatile method for varying the magnetization degrees of individual living cells, as micro-magnets, while maintaining the cell viability.…”
mentioning
confidence: 99%
“…The polymer exterior formed via above strategies acts as a “soft shell”, which may significantly alter the properties of cell surface, but is not necessarily robust enough to fight against mechanical attacks, heat or radiant threats [43, 6468]. It has been found that natural systems choose hard and tough shell structures [20, 21] to enhance their survivability under harsh conditions.…”
Section: Approaches For Cell Nanomodificationmentioning
confidence: 99%
“…It has been found that natural systems choose hard and tough shell structures [20, 21] to enhance their survivability under harsh conditions. Inspired by natural structures, artificial hard shells have been utilized to increase heat tolerance and radiation resistance of some single-cellular livings by means of their physicochemical durability and biological stability [43, 64, 65]. Microorganisms, such as cyanobacteria which are a general study model for cellular biology, can induce a uniform silica shell with the help of suitable polymer coating (Fig.…”
Section: Approaches For Cell Nanomodificationmentioning
confidence: 99%
“…Biointerfaces are the key feature of many biotechnological 1 and plasma medicine 2 devices and techniques based on biologically active substances such as plant and animal cells, 3,4 biofilms, 5 and bacterial cultures, 6 bioethanol-producing bacteria 7 and stem cells, 8 DNA, 9 red blood cells, 10 biomolecules, 11 and proteins and enzymatic biocatalysts. 12,13 Biointerfaces are also of a major importance for various industrial applications including fluidised bed bioreactors, 14 food processing 15 and energy conversion devices, [16][17][18] biosensors 19 and sensors, 20 virus detection, 21 biofuel cells, 22 drug delivery devices, 23 and microfluidic 24 and fixed-bed catalytic reactors.…”
Section: Introductionmentioning
confidence: 99%